Real-life experience of infliximab biosimilar in pediatric-onset inflammatory bowel disease: data from the Sicilian Network for Inflammatory Bowel Disease. Issue 10 (14th July 2022) - Dipasquale, Valeria; Pellegrino, Salvatore; Ventimiglia, Marco; Cucinotta, Ugo; Citrano, Michele; Graziano, Francesco; Cappello, Maria; Busacca, Anita; Orlando, Ambrogio; Accomando, Salvatore; Romano, Claudio; ,
Abstract : Objective: To provide data on the use of infliximab biosimilars (IFX-BioS) in children with inflammatory bowel disease (IBD). Methods: A multicenter, observational, retrospective study was performed among the cohort of the Sicilian Network for IBD. All consecutive IBD children who had at least completed the induction with IFX-BioS from its introduction in Sicily to January 2021 were enrolled. Clinical remission at weeks 14 and 52, treatment persistence, and adverse events were the study outcomes. Results: Eighty-seven patients [Crohn's disease (CD): 57.5% and ulcerative colitis (UC): 42.5%] were included: 75 (86.2%) were antitumor necrosis factor-α (anti-TNF-α) agent naïve, while three (3.45%) were switched from the originator to IFX-BioS. Twenty (23%) patients were multiply switched from the biosimilar CT-P13 to SB2 or GP1111 or vice versa. The median follow-up time was 15 months. Clinical remission was achieved by 55.2 and 65.5% of patients at weeks 14 and 52, respectively, with no differences between CD and UC. Dose escalation was needed in 8.0 and 35.7% of patients during induction and maintenance, respectively. Nine adverse events occurred (incidence rate: 6.13/100 person-year). Treatment persistence was 90.8% at 1 year and 75.7% at 2 years (patients on IFX-BioS at 2 years, n = 28). The risk of treatment discontinuation was higher in patients with extraintestinal manifestations ( P = 0.018) and in those who were nonnaïve to anti-TNF-α ( P = 0.027). Conclusion: This is the largest cohort of pediatric IBD patients treated with IFX-BioS. Real-life data show that IFX-BioS is efficacious in IBD children, with high percentages of treatment persistence and a low incidence of nonserious adverse events.